Weaning Practice in Children with Iron Deficiency Anemia - Abbasi, Maryam; Aziz, Khawaja Tahir; Abbasi, Amna (Indus Journal of Bioscience Research, 2025)
Background: Weaning, also called as supplemental feeding, is the process of progressively reducing nursing or bottle-feeding while introducing solid meals to newborns. Methodology: A cross-sectional comparative design was used to carry out this cross-sectional investigation. To assess the weaning practices, feeding habits, and hematological profiles of two groups of children, one with iron deficiency anemia and the other without IDA. This study contrasts them at different points in time. IBM SPSS was used to analyze the data. 129 kids without iron deficiency anemia and 65 kids with it took part in the study. The association between early and late weaning and iron deficiency anemia (IDA) and non-IDA was evaluated using the chi-square test. The association between continuous variables, such as ferritin levels and the period between weaning and proper food intake, as well as the association between the weaning interval and children’s hemoglobin levels, was investigated using correlation statistical tests. Results: Iron deficiency anemia (IDA) was reported by 33.3 percent of individuals, with pallor being the most prevalent symptom (33.8%). 44.6 percent weaned early, while 29.2% weaned late. IDA was a significant association with late weaning (p=0.00). There was a strong negative correlation between delayed adequate nutrition introduction and ferritin (r=-0.33, P=0.00, showing that the risk of having iron deficiency anemia (IDA). Conclusion: The findings demonstrate a strong association between delayed weaning and iron deficiency anemia (IDA) in children; late weaning is linked to emphasizes the significance of prompt and appropriate weaning to avoid IDA.